The Simon van der Stel Festival : constructing heritage and the politics of pageantry (Historia, 2021)
The Simon van der Stel Festival was celebrated as an annual event in Stellenbosch from 1967 to 2000, celebrating the town's colonial-Dutch heritage in the form of a birthday celebration dedicated to its founder. In particular the focus of this article falls on the reasons why such a festival was initiated and why Stellenbosch lent itself perfectly to the hosting of the event. Furthermore, its progress is tracked until its climax in 1979, which was the tercentenary festival that celebrated 300 years since the founding of Stellenbosch. Heritage construction, pageantry and "the cult of the centenary" are used to explain why this festival was launched; the significance of hosting such a festival in Stellenbosch; how it changed over time; who was actively involved in its organisation; what the implications were of hosting such a festival; and why the festival eventually came to an end. Moreover, the Simon van der Stel Festival will be compared to a similar festival - the Jan van Riebeeck Festival of 1952 - which celebrated the founding of Cape Town in a similar fashion, but with more overt nationalist overtones.  Die Simon van der Stel Fees was geïmplementeer as 'n jaarlikse geleentheid in Stellenbosch vanaf 1967 tot 2000, as 'n viering van die dorp se Nederlandse koloniale erfenis in die vorm van 'n verjaarsdag-viering van sy stigter. Die fokus van hierdie artikel val op die redes waarom so 'n fees geïnisieer was asook waarom Stellenbosch uitgeknip was tot die aanbieding van so 'n fees. Verder word die vordering van die fees nagespoor tot en met die hoogtepunt in 1979, wat 300 jaar sedert die stigting van Stellenbosch gevier het. Erfenis konstruksie, "pageantry" en die "kultus van die eeufees" word gebruik om te verduidelik waarom so 'n fees gestig was; die betekenis van so 'n fees op Stellenbosch; hoe dit verander het met tyd; wie was verantwoordelik vir die organisasie van die fees; wat die implikasies was om so 'n fees te behartig; asook waarom die fees tot 'n einde gekom het. Laastens word die Simon van der Stel Fees vergelyk met 'n soortgelyke fees, naamlik die Jan van Riebeeck Fees van 1952, wat die stigting van Kaapstad gevier het, alhoewel met meer openlike nasionalistiese ondertone.
Keywords: Feeste; Simon van der Stel; Nederlandse koloniale Kaap; Jan van Riebeeck